Key clinical evidence about current topical treatments for venous leg ulcers: a systematic review (Research, Society and Development, 2022)
Objective: To analyze the main clinical evidence about current topical treatments for venous leg ulcers. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “venous ulcer”, “topical treatment”, “topical management”, “topical wound care” and “dressing”. Full texts, available in Portuguese, English or Spanish, published between January 2018 and July 2022 were included. In addition to these criteria, only studies that addressed topical wound care products for the management of venous leg ulcers were included. Results: 12 articles made up the final sample of this study, with the highest production in 2020 (n: 05). A remarkable variety of topical products has been found for the treatment of venous leg ulcers: dehydrated human amnion/chorion membrane allograft, autologous platelet-rich plasma, concentrated growth factors, centrifuged adipose tissue, biopolymer membrane of natural matrix, collagenase coverage, 2-4% papain with Unna's boot, topical timolol, 0.9% cadexomer iodine ointment and hyaluronic acid. Conclusion: Several topical products for the treatment of venous leg ulcers were identified in the scientific literature, showing positive results in relation to healing, reduction of the lesion area and improvement of pain in affected patients.